532. INDOCYANINE GREEN FLUORESCENCE DETECTED THE IMPAIRED BLOOD FLOW IN THE GASTRIC CONDUIT WITH ULCER SCARS: A PROSPECTIVE PRELIMINARY STUDY. (24th September 2022) - Ichikawa, Hiroshi; Muneoka, Yusuke; Usui, Kenji; Kano, Yosuke; Ishikawa, Takashi; Hirose, Yuki; Miura, Kohei; Tajima, Yosuke; Shimada, Yoshifumi; Sakata, Jun; Kosugi, Shin-ichi; Wakai, Toshifumi
Abstract: We previously identified the presence of peptic or endoscopic submucosal dissection (ESD) ulcer scars in the stomach as a risk factor for anastomotic leakage of esophagogastric anastomosis after esophagectomy. In this study, we investigated the association between peptic or ESD ulcer scars and blood flow at the gastric conduit using indocyanine green (ICG) fluorescence imaging. We prospectively enrolled 17 patients who underwent cervical esophagogastric anastomosis after esophagectomy for thoracic esophageal cancer (15 men and 2 women with a median age of 70 years). Blood flow in the wall of gastric conduit was evaluated using ICG fluorescence imaging detected by a near-infrared camera system during the operation. The flow velocity of ICG fluorescence in the gastric wall was calculated by dividing the distance (cm) by moving time of ICG fluorescence (second) from the pylorus to the point of final branch of the right gastroepiploic artery. In 17 patients, four had peptic or ESD ulcer scars in the stomach. One patient with ESD ulcer scars in the lesser curvature side resected during the creation of conduit was included in 13 without ulcer scars. The median flow velocity was significantly lower in patients with ulcer scars than that in patients without ulcer scars (1.15 cm/s vs. 2.17 cm/s, P < 0.01). Anastomotic leakage was occurred only in two patients; one had ESD ulcer scar in the greater curvature side with the velocity of 1.17 cm/s, and one had no ulcer scars with the velocity of 1.67 cm/s. Peptic or ESD ulcer scars were associated with the impaired blood flow in the wall of gastric conduit. Intraoperative ICG fluorescence imaging is a promising modality to evaluate the risk of anastomotic leakage after esophagectomy.